PEMANFAATAN DANA DESA UNTUK PENINGKATAN TARAF HIDUP MASYARAKAT PEDESAAN MELALUI PEMBERDAYAAN MASYARAKAT DESA - Rumsari Hadi Sumarto; Lukas Dwiantara (Universitas Halu Oleo, 2019)
Development is carried out to improve the standard of living of its citizens. Development is also carried out so that there is no disparity between villages and cities. The rapid development in urban areas which has triggered a wave of urbanization has made the villages increasingly marginalized. Urbanization flows are difficult to stem because the village mindset assumes that in the city they will get jobs so they can improve their standard of living. With this phenomenon, the Government rolled out the Village Fund Policy. The Village Fund Policy opens employment opportunities in the village so that the community can be empowered through development programs in the village. The purpose of this paper is to describe the empowerment of rural communities through the Village Fund so that they can improve the living standard of rural communities. This paper uses a type of library research through documents analysis such as data contained in various media, books and other documents. The use of the Village Fund is significant to prevent the flow of urbanization. Opportunities for village communities to improve living standards were accommodated through community empowerment from the Village Fund. Keywords: Village Funds, Empowerment, Improvement of Life Level